Mechanical and thermal properties of biphenyldiol formaldehyde resin/gallic acid epoxy composites enhanced by graphene oxide. Issue 41 (14th July 2015) - Chen, Shihui; Lv, Shufang; Hou, Guixiang; Huo, Li; Gao, Jungang
ABSTRACT In this study, the gallic acid‐based epoxy resin (GA‐ER) and alkali‐catalysed biphenyl‐4, 4′‐diol formaldehyde resin (BPFR) are synthesized. Glass fibre‐reinforced GA‐ER/BPFR composites are prepared. Graphene oxide (GO) is used to improve the mechanical and thermal properties of GA‐ER/BPFR composites. Dynamic mechanical properties and thermal, mechanical, and electrical properties of the composites with different GO content are characterized. The results demonstrate that GO can enhance the mechanical and thermal properties of the composites. The glass transition temperature, Tg, of the BPFR/GA‐ER/GO composites is 20.7°C higher than the pure resin system, and the 5% weight loss temperature, Td5, is enhanced approximately 56.6°C. When the BPFR: GA‐ER mass ratio is at 4 : 6 and GO content is 1.0–1.2 wt %, the tensile and impact strengths of composites are 60.97 MPa and 32.08 kJ/m2 higher than the pure resin composites, respectively. BPFR/GA‐ER composites have better mechanical properties, and can replace common BPA epoxy resins in the fabrication of composites. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42637.